A Catalogue of Marine Biodiversity Indicators - Teixeira, Heliana; Berg, Torsten; Uusitalo, Laura; Fürhaupter, Karin; Heiskanen, Anna-Stiina; Mazik, Krysia; Lynam, Christopher P.; Neville, Suzanna; Rodriguez, J. German; Papadopoulou, Nadia; Moncheva, Snejana; Churilova, Tanya; et al. (Frontiers in Marine Science, 2016)
A Catalogue of Marine Biodiversity Indicators was developed with the aim of providing the basis for assessing the environmental status of the marine ecosystems. Useful for the implementation of the Marine Strategy Framework Directive (MSFD), this catalogue allows the navigation of a database of indicators mostly related to biological diversity, non-indigenous species, food webs, and seafloor integrity. Over 600 indicators were compiled, which were developed and used in the framework of different initiatives (e.g. EU policies, research projects) and in national and international contexts (e.g. Regional Seas Conventions, and assessments in non-European seas). The catalogue reflects the current scientific capability to address environmental assessment needs by providing a broad coverage of the most relevant indicators for marine biodiversity and ecosystem integrity. The available indicators are reviewed according to their typology, data requirements, development status, geographical coverage, relevance to habitats or biodiversity components, and related human pressures. Through this comprehensive overview, we discuss the potential of the current set of indicators in a wide range of contexts, from large-scale to local environmental programs, and we also address shortcomings in light of current needs. Developed by the DEVOTES Project, the catalogue is freely available through the DEVOTool software application, which provides browsing and query options for the associated metadata. The tool allows extraction of ranked indicator lists best fulfilling selected criteria, enabling users to search for suitable indicators to address a particular biodiversity component, ecosystem feature, habitat or pressure in a marine area of interest. This tool is useful for EU Member States, Regional Sea Conventions, the European Commission, non-governmental organizations, managers, scientists and any person interested in marine environmental assessment. It allows users to build, complement or adjust monitoring programs and has the potential to improve comparability and foster transfer of knowledge across marine regions.